(untitled) (Emergency Care Journal, 2022)
A 38-year-old man presented to our emergency room with severe pain and inability to mobilize his right shoulder joint after a violent blunt trauma during his work. The humeral head was palpable anteriorly, with the loss of normal contour of the deltoid and acromion prominent posteriorly and laterally, as it occurs in the anterior shoulder dislocation. The shoulder was easily reduced on 1st attempt using 1.5 mg/kg intravenous fentanyl and 0.5 mg/Kg intravenous midazolam sedation in the emergency room. After the procedure, he complained of pain at the right humeral head, so we performed an X-Ray.